Peningkatan Kemampuan Public Speaking Mahasiswa Prodi Sastra Inggris dan Prodi Sastra Indonesia Fakultas Ilmu Budaya Universitas Lancang Kuning - Edawrd Edawrd; Sorta Hutahaean (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2022)
This article is entitiled, “The Improvement of student’s ability in publc speaking at Department of Indonesia and English Literature, Faculty of Humanities, Lancang Kuning University. The research was aimed at improving the ability of the students in Public Speaking using mixed and contextual method. After doing the treatment it was found that students were knowledgeable in terms of language use and in using the style and diction accordingly when speaking before the audienc.